2005
DOI: 10.1301/nr.2005.nov.374-386
|View full text |Cite
|
Sign up to set email alerts
|

Components of Olive Oil and Chemoprevention of Colorectal Cancer

Abstract: Olive oil contains a vast range of substances such as monounsaturated free fatty acids (e.g., oleic acid), hydrocarbon squalene, tocopherols, aroma components, and phenolic compounds. Higher consumption of olive oil is considered the hallmark of the traditional Mediterranean diet, which has been associated with low incidence and prevalence of cancer, including colorectal cancer. The anticancer properties of olive oil have been attributed to its high levels of monounsaturated fatty acids, squalene, tocopherols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
4
24
0
1
Order By: Relevance
“…For example, linoleic acid and oleic acid can inhibit cell proliferation and induce apoptosis in HT29 cells [96]. Consumption of olive oil, which is high in oleic acid that can activate PPAR β / δ (Table 1), has also been associated with a decreased risk of colon cancer [97,98]. However, other components of olive oil, such as phenolic compounds, may contribute to this chemopreventive association [98].…”
Section: Effect Of Ligand Activation Of Pparβ/δ In Colon Cancer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, linoleic acid and oleic acid can inhibit cell proliferation and induce apoptosis in HT29 cells [96]. Consumption of olive oil, which is high in oleic acid that can activate PPAR β / δ (Table 1), has also been associated with a decreased risk of colon cancer [97,98]. However, other components of olive oil, such as phenolic compounds, may contribute to this chemopreventive association [98].…”
Section: Effect Of Ligand Activation Of Pparβ/δ In Colon Cancer Modelsmentioning
confidence: 99%
“…Consumption of olive oil, which is high in oleic acid that can activate PPAR β / δ (Table 1), has also been associated with a decreased risk of colon cancer [97,98]. However, other components of olive oil, such as phenolic compounds, may contribute to this chemopreventive association [98]. Chemopreventive associations between a high intake of eicosapentaenoic acid or docosahexaenoic acid and colon cancer are well documented [99], and both of these fatty acids can also activate PPAR β / δ (Table 1).…”
Section: Effect Of Ligand Activation Of Pparβ/δ In Colon Cancer Modelsmentioning
confidence: 99%
“…Olive oil, oleuropein, and its derivatives have a variety of biochemical roles, including antiinflammatory effects (10)(11)(12)(13)(14), antithrombic actions (15), prevention of LDL oxidation (16,17) and platelet aggregation (18), antihyperglycemic activity (19), and antiischemic and hypolipidemic effects (20). Furthermore, it has been reported that oleuropein and/or olive oil inhibited tumor growth (21)(22)(23)(24) and that the topical application of olive oil prevented UVB-induced carcinogenesis (25,26). However, the effects of an orally administered olive leaf extract and its main component oleuropein on long-term UVB-induced photoaging (for example, increases in skin thickness and reductions in skin elasticity) and carcinogenesis have not been fully studied in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several epidemiological and interventional studies, supported by in vitro and in vivo evidence, have demonstrated that its dietary consumption is associated with a decreased incidence of cardiovascular disease, coronary heart disease (CHD) and cancers such as breast, colorectal and prostate cancer (Keys, 1995;Owen et al, 1995;Hashim et al, 2005).…”
mentioning
confidence: 99%
“…Recent findings suggest that the chemopreventive effect of olive oil can be attributed to the antioxidant properties of its polyphenol constituents (Owen et al, 1995;Hashim et al, 2005).…”
mentioning
confidence: 99%